Independence and effectiveness in internal shariah audit with insights drawn from Islamic agency theory - Azam Abdelhakeem Khalid (Tanjung Malim, 2021)
Independence and effectiveness in internal shariah audit with insights drawn from Islamic agency theory by Azam Abdelhakeem Khalid